ANALISIS PENGARUH METODE AKUNTANSI PERSEDIAAN TERHADAP PRICE EARNING RATIO - SISCA LAGIANTO; MURTANTO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2004)
The objective of this study is identify the identify the factors which are influent the choice of inventory method and its effect to price earning ratio with the focus to Ricardian hypotheses. The study will examine regarding the choice of inventory method between average and FIFO method. This examination used six variables are: inventory variability, firm size, and accounting income variability. The object of this study are all manufacturing companies listed in BEJ during 2000-2002. The t-test, Mann whitney, logistic regression, and analysis of covariance used to test of hypotheses. The result of the logistic regression shows that production investment opportunity is influent to the inventory method choice. The Mann Whitney test and analysis of covariance shows that firms price price earning ratio between FIFO and Average method are not significant although using control variable.